CAREER GUIDANCE PRACTICES UNDER THE CONDITIONS OF GLOBALISATION: A SOCIOLOGICAL ANALYSIS - G. F. Shafranov-Kutsev; G. Z. Efimova; M. Yu. Semenov (Russian State Vocational Pedagogical University, 2018)
Introduction. In the context of globalisation, competition for high quality and highly effective human capital is increasing. Successful training of highly qualified specialists is impossible without an adequate system of professional orientation of young people that is implemented at all levels of the educational system and expressed in real career guidance practices. Thus, the relevance of scientific understanding and analysis of career guidance activities carried out in modern times is manifested.The aim of the publication was the study of modern vocational guidance practices present and prevailing in the educational system of the Russian Federation, taking into account world experience.Methodology and research methods. At the theoretical stage, the review and generalisation of scientific publications relevant to the stated theme and objectives of the research were carried out. To study career guidance practices, a questionnaire survey intended for high school students (1087 students of secondary rural, municipal and elite schools) of the Tyumen region was conducted. A selective secondary analysis of sociological studies published by the Russian and foreign scholars was undertaken. Results and scientific novelty. Global trends in career guidance were designated; real examples of the positive experience accumulated by other countries in this sphere were reviewed. The most burning issues of the implementation of career guidance activity in the Russian education system were identified. On the basis of sociological survey, the leading motives of professional choice by high school students were established. It was determined that those motives vary according to a status, a type and a territory of educational institution in which students study. The differences in students' degree of satisfaction with career guidance actions were shown. The authors conclude that to avoid labour market distortions and many other social problems, it is necessary to concentrate the center of gravity of career guidance work on the general education; therefore, during this period the foundation for professional self-determination of a person is provided. It is necessary to shift the vector of implementation of career guidance practices in the system of general education with the identification of students' capabilities and predispositions, to inform and to involve them in the world of professions (e.g. employment practices, meetings with representatives of different specialties and employers, as well as other forms and types of career guidance both inside and outside school). The authors propose the creation of federal platform on the principles of voluntary interaction of all interested parties in order to strengthen the role of vocational guidance of the younger generation and to provide students with timely valuable informational and advisory support.Practical significance. The materials and conclusions of the research can be used when developing effective recommendations to strengthen the process of professional orientation of young people in the education system.